(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The mountain crusher is the highest loaded and bulk of the drilling equipment. Much of the contribution of the operational efficiency of drilling equipment is due to the work of mountain precision flicker tools, and it has been found that many factors influence the work of a mountain flicker tool.